Ekranisasi Novel Dignitate Karya Hana Margaretha ke Film Dignitate Sutradara Fajar Nugros - Lailatul Amal; Emilda Rani; Ardesa Pratiwi (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe the ecranization of Hana Margaretha's novel "Dignitate" into the film "Dignitate." The various reductions, additions, and changes to the storyline are found in Hana Margaretha's novel "Dignitate" and the film "Dignitate." This study uses a qualitative approach, and this approach is descriptive qualitative. The data for this study are excerpts from paragraphs, dialogues, and sentences containing ecranization in Hana Margaretha's novel "Dignitate" and the film "Dignitate." The data collection technique for this study was reading and note-taking. Based on the results, 37 data were found, including 27 reductions, 8 additions, and 2 changes. The most significant data in this study is the reduction.